2021
DOI: 10.1186/s12884-021-03705-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of congenital microcephaly and its risk factors in an area at risk of Zika outbreaks

Abstract: Background Prevalence of neonatal microcephaly in populations without Zika-epidemics is sparse. The study aimed to report baseline prevalence of congenital microcephaly and its relationship with prenatal factors in an area at risk of Zika outbreak. Methods This study included singletons born after 24 gestational weeks in 2017–2018 at four hospitals in Guangzhou, China. Microcephaly was defined as a head circumference at birth >3SD below the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…It was also 1.5 times higher than reported in Brazil (60 cases per 10,000 births) at the peak of the ZIKV outbreak in 2016. However, a study in China reported a higher prevalence of 410 cases per 10,000 births [ 30 ]. None of the newborns with microcephaly in our study had evidence of ZIKV and only one had confirmed DENV exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It was also 1.5 times higher than reported in Brazil (60 cases per 10,000 births) at the peak of the ZIKV outbreak in 2016. However, a study in China reported a higher prevalence of 410 cases per 10,000 births [ 30 ]. None of the newborns with microcephaly in our study had evidence of ZIKV and only one had confirmed DENV exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The two cities, Quebec and Guangzhou, had no documented evidence of ZIKV infection at the time these studies took place [ 26 , 27 ]. A second study in Guangzhou included 46,610 live births between 2017–2018 and identified 154 microcephaly cases [ 28 ]. The authors showed that maternal hepatitis B virus infection, primiparous mothers, preterm labor, and fetal growth restriction were main drivers of microcephaly cases [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A second study in Guangzhou included 46,610 live births between 2017–2018 and identified 154 microcephaly cases [ 28 ]. The authors showed that maternal hepatitis B virus infection, primiparous mothers, preterm labor, and fetal growth restriction were main drivers of microcephaly cases [ 28 ]. Although it was the first time that maternal exposure to congenital hepatitis B virus infection has been associated with microcephaly [ 28 ], the strength of its effect on microcephaly risk ( RR = 1.62) is lower than the risks from maternal infection by TORCH ( RR = 4.29–31.17), as shown by [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital microcephaly (CM) is defined as having an occipitofrontal circumference (OFC) that is more than two standard deviations (SDs) below the mean at birth for gestational age and sex [1, 2]; and the prevalence is reported to be 1–33 per 10,000 live births [3, 4]. Neurological abnormalities are usually associated with CM [5, 6].…”
Section: Introductionmentioning
confidence: 99%